2020
DOI: 10.1534/g3.119.401031
|View full text |Cite
|
Sign up to set email alerts
|

Loss of N-Glycanase 1 Alters Transcriptional and Translational Regulation in K562 Cell Lines

Abstract: N-Glycanase 1 (NGLY1) deficiency is an ultra-rare, complex and devastating 15 neuromuscular disease. Patients display multi-organ symptoms including developmental delays, 16 movement disorders, seizures, constipation and lack of tear production. NGLY1 is a 17 deglycosylating protein involved in the degradation of misfolded proteins retrotranslocated from 18 the endoplasmic reticulum (ER). NGLY1-deficient cells have been reported to exhibit decreased 19 deglycosylation activity and an increased sensitivity to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 53 publications
5
19
0
Order By: Relevance
“…Similar downregulation at the transcriptional level of proteasomal subunits was also observed following NGLY1 KD in human K562 cells and was interpreted as related to reduced post-translational processing of NFE2L1 to the mature transcription factor NRF1 by NGLY1 (Mueller et al, 2020). Consistent with these observations it was found that NGLY1 disruption sensitizes towards proteasome inhibition by bortezomib in human cells (Mueller et al, 2020) and Drosophila larvae (Rodriguez et al, 2018). The NGLY1 KO mouse model showed the importance of the genetic background towards embryonic lethality and demonstrated that concomitant KO of the Engase gene partially rescued embryonic lethality in C57BL/6 mice (Fujihira et al, 2017).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Similar downregulation at the transcriptional level of proteasomal subunits was also observed following NGLY1 KD in human K562 cells and was interpreted as related to reduced post-translational processing of NFE2L1 to the mature transcription factor NRF1 by NGLY1 (Mueller et al, 2020). Consistent with these observations it was found that NGLY1 disruption sensitizes towards proteasome inhibition by bortezomib in human cells (Mueller et al, 2020) and Drosophila larvae (Rodriguez et al, 2018). The NGLY1 KO mouse model showed the importance of the genetic background towards embryonic lethality and demonstrated that concomitant KO of the Engase gene partially rescued embryonic lethality in C57BL/6 mice (Fujihira et al, 2017).…”
Section: Discussionsupporting
confidence: 60%
“…The study in the Drosophila model also showed evidence for cnc (fly ortholog of NRF1) dysfunction by transcriptome analysis among downregulated genes (such as those encoding for proteasomal subunits) and an upregulation of the heat shock response (Owings et al, 2018). Similar downregulation at the transcriptional level of proteasomal subunits was also observed following NGLY1 KD in human K562 cells and was interpreted as related to reduced post-translational processing of NFE2L1 to the mature transcription factor NRF1 by NGLY1 (Mueller et al, 2020). Consistent with these observations it was found that NGLY1 disruption sensitizes towards proteasome inhibition by bortezomib in human cells (Mueller et al, 2020) and Drosophila larvae (Rodriguez et al, 2018).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…While perturbations to ERAD often result in ER stress, we have previously reported that there was no functional or transcriptome evidence for ER stress in a Drosophila model of NGLY1 deficiency ( Owings et al, 2018 ). Others have reported no ER stress in NGLY1 -/- human cells, mice, and rats ( Asahina et al, 2020 ; Mueller et al, 2020 ; Tambe et al, 2019 ). However, there is conflicting evidence for ER stress as it was recently reported that ER stress markers were upregulated in NGLY -/- MEFs ( Galeone et al, 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that model substrates can be degraded regardless of glycosylation state (Hirsch et al, 2003;Kario, Tirosh, Ploegh, & Navon, 2008). While a recent report showed that ER stress markers were increased in NGLY1 -/-MEFs (Galeone et al, 2020), other experiments such as RNAi knockdown of NGLY1 in Drosophila, (Owings, Lowry, Bi, Might, & Chow, 2018) and loss of NGLY1 function in mouse, rat, and human cells (Asahina et al, 2020;Mueller et al, 2020;Tambe, Ng, & Freeze, 2019) have shown no evidence of ER stress. ER stress is often observed when there are mutations in proteins that are necessary for ERAD due to the accumulation of misfolded proteins in the ER.…”
Section: Introductionmentioning
confidence: 99%